A Geoelectrical Study of Aquifers in the Natar Region, South Lampung - Rahmi Mulyasari; I Gede Boy Darmawan; Hesti Hesti; Akroma Hidayatika; Suharno Suharno (Journal of Engineering and Scientific Research, 2022)
The conditions for the development of population growth and development in the area around the City of Bandar Lampung are very fast and starting to get crowded, as happened in the District of Natar South Lampung, especially in the Village of Pemanggilan. This condition causes an increase in the need for clean water resources in line with the increase in groundwater exploitation. Therefore it is necessary to map the potential of groundwater through aquifer mapping and aquifer rock layers through geoelectrical measurements. This study aims to determine the potential of groundwater from volcanic aquifer systems based on geoelectrical measurements. The method used in this study is geoelectric resistivity using the Wenner-Schlumberger configuration with 3 measurement points. The results of the study show that using the geoelectrical resistivity method, layers with a resistivity value of ? 30.3 ?m are interpreted as shallow aquifers at depths varying from 1 to more than 24 meters with lithology suspected to be tuff and tuff sandstones, which according to geological data are included in the Lampung Formation. Using the 2D geoelectric method, the distribution of shallow aquifers in the study area to a depth of 24 meters can also be determined. The data obtained is expected to be used as supporting data for the sustainable use of water sources.